Marketing Analytics Capability and ERP Systems Implementation: Theoretical Framework and Case Study - Dar, Imran Bashir; Khan, Prof Dr. Muhammad Bashir; Shafiq, Dr. Muhammad; Ali, Manzoor (The journal of contemporary issues in business and government, 2021)
ERP systems implementation through investment in marketing analytics capabilities (MACs) is imperative in Industry 4.0 age. The theoretical framework is developed and utilised for mapping the case study of a nationally well-renowned ERP consultancy strategic business unit (SBU) of FCL. The FCL uses marketing analytics capability for ERP projects’ implementation and consultancy around Pakistan. It is one of the few companies that have complete structure for SAP EPR solutions. The Marketing Analytics Capability Framework (MACF) for this case study is composed of Culture Capability (CC), Technology Capability (TC), and People Capability (PC), along with ERP implementation cycle. The team heads and experts, with notable experience, were interviewed, through operationalisation of non-probability purposive sampling. A holistic view of MACs for ERP implementation, through paradigm lens of big data business analytics (BDBA) is presented.